Pore Structure Characteristics and Evolution Law of Different-Rank Coal Samples - Zhihui Wen; Qi Wang; Yunpeng Yang; Leilei Si (Geofluids)
In this study, the full-size pore structure characteristics of six different-rank coal samples were investigated and analyzed from three perspectives, namely, pore shape, pore volume, and pore specific surface area, by performing a high-pressure mercury injection experiment and a low-temperature nitrogen adsorption experiment. Next, the full-size pore volumes and pore specific surface areas of the six coal samples were accurately characterized through a combination of the two experiments. Furthermore, the relationships between volatile matter content and pore volume and between volatile matter content and pore specific surface area were fitted and analyzed. Finally, the influences of metamorphic degree on pore structure were discussed. The following conclusions were obtained. The pore shapes of different-rank coal samples differ significantly. With the increase of metamorphic degree, the full-size pore volume and pore specific surface area both decrease first and then increase. Among the pores with various sizes, micropores are the largest contributor to the full-size pore volume and pore specific surface area. The fitting curves between volatile matter content and pore volume and between volatile matter content and pore specific surface area can well reflect the influence and control of metamorphic degree on pore volume and pore specific surface area, respectively. With the increase of volatile matter content, the pore volume and the pore specific surface area both vary in a trend resembling a reverse parabola.